Correlation Between Hydration Status and Renal Ultrasonographic Parameters: A Cross-Sectional Study - Wahyu Hidayat; Nurbaiti Nurbaiti; Sriyatun Sriyatun; Puji Supriyono; Minda Fitrah Riwanda; Puspa Pamella Suci (Media Publikasi Cendekia Indonesia, 2026)
The kidneys play a critical role in maintaining fluid homeostasis, and suboptimal hydration may lead to morphological alterations detectable via imaging. This study aimed to analyze the correlation between hydration status and various renal ultrasonographic parameters. An observational, cross-sectional study was conducted with 30 healthy radiology students selected through purposive sampling. Hydration status was evaluated using the Perceived Urine-Richness Index (PURI) based on morning urine color. Renal ultrasound examinations were performed to assess kidney size, parenchymal echogenicity, corticomedullary differentiation, and resistive index. Data were statistically analyzed using the Chi-Square test with a significance threshold of p<0.05. The assessment revealed that 76.7% of participants had low to very low hydration levels. Statistical analysis demonstrated that parenchymal echogenicity was the only parameter significantly correlated with hydration status (p=0.001 for the right kidney; p=0.004 for the left kidney). Other ultrasonographic markers, including kidney length, cortical thickness, and resistive index (RI), showed no significant association with hydration levels. Hydration status is significantly associated with changes in renal parenchymal echogenicity, identifying it as a sensitive, non-invasive marker for early renal stress and subclinical morphological changes. These findings underscore the necessity of maintaining adequate fluid intake to preserve renal structural integrity as visualized through ultrasonography.